Aboriginal University Student Success in British Columbia, Canada: Time for Action - Oloo, James Alan (The Australian Journal of Indigenous Education, 2007)
Abstract Educational outcomes for Aboriginal students in British Columbia, and Canada in general, are a cause for considerable concern. High dropout rates, low participation, completion and success rates at educational institutions have challenged educators for decades. Solutions have included lowering admission requirements for Aboriginal candidates and establishing alternative programmes that improve attendance and remedy learning problems. However, most of these policies have not offered a lasting solution to challenges facing Aboriginal students. This study presents findings from interviews conducted with 20 Aboriginal undergraduate students, seven professors, and five non-academic staff at four universities in British Columbia, namely: Malaspina University College, University of Victoria, University of British Columbia, and Simon Fraser University. It presents their definitions of student success and how this could be improved. Four policy options are proposed. These are then tested against six criteria to determine the potential consequences of their implementation. Recommendations are made to British Columbia’s universities based on the multicriteria analysis.